PERANCANGAN SIMULASI ALAT PENGUKURAN INTENSITAS CAHAYA MENGGUNAKAN LUX METER BERBASIS LDR DAN ARDUINO DENGAN PENGATURAN LED - NURANI, ANNISA EKMA; Kuspranoto, Abdul Haris (MEDIKA TRADA : Jurnal Teknik Elektomedik Polbitrada, 2023)
Light is a visible electromagnetic wave whose main function is to illuminate the environment. Light has a significant impact on the human eye. A lux meter can be used to check the intensity of light. However, cheaper and more accurate light meters are not currently available. The design simulation of this tool is carried out to simulate accuracy and efficiency. The simulation involves the design of a more efficient light intensity measurement tool with a lux meter. The Luxmeter is equipped with a photoresistor sensor to read the intensity of light and an LED for the standard light intensity measurement system. The control system of this lux meter is operated by an Arduino Uno, and the readings of light intensity and distance can be displayed on a 20x4 LCD. The simulation of this tool is conducted to determine the accuracy of the light intensity and distance measurements.